Increased Risk of Decompression Sickness When Diving With a Right-to-Left Shunt: Results of a Prospective Single-Blinded Observational Study (The “Carotid Doppler” Study) - Germonpré, Peter; Lafère, Pierre; Portier, William; Germonpré, Faye-Lisa; Marroni, Alessandro; Balestra, Costantino (Frontiers in Physiology, 2021)
Introduction Divers with a patent Foramen Ovale (PFO) have an increased risk for decompression sickness (DCS) when diving with compressed breathing gas. The relative risk increase however, is difficult to establish as the PFO status of divers is usually only determined after a DCS occurrence. Methods This prospective, single-blinded, observational study was designed to collect DCS data from volunteer divers after screening for right-to-left shunt (RLS) using a Carotid Doppler test. Divers were blinded to the result of the test, but all received a standardized briefing on current scientific knowledge of diving physiology and ‘low-bubble’ diving techniques; they were then allowed to dive without restrictions. After a mean interval of 8 years, a questionnaire was sent collecting data on their dives and cases of DCS (if any occurred). Results Data was collected on 148 divers totaling 66,859 dives. There was no significant difference in diving data between divers with or without RLS. Divers with RLS had a 2.65 times higher incidence of DCS than divers without RLS. DCS occurred mainly in divers who did not dive according to ‘low-bubble’ diving techniques, in both groups. Conclusion This prospective study confirms that DCS is more frequent in divers with RLS (such as a PFO), with a relative risk of 2.65. It appears this risk is linked to diving behavior, more specifically diving to the limits of the adopted decompression procedures.